Undeclared Work in Poland: Characteristics and Prevalence - Nikulin, Dagmara (Ekonomika, 2016)
This article aims to present the significance and prevalence of the phenomenon of undeclared work. First, we discuss the definitional issues of this phenomenon. Then, we present previous estimates on shadow economy and undeclared work in Poland, based on statistics provided by Central Statistical Office and other research entities. Our analysis covers the years 2000–2014. In the last part of the article, we use data from the Labour Force Survey in Poland to measure the number of unemployed who work informally. We show a decrease in number of this specific type of informal workers. In the next step, we compare our estimates with the total number of informal employees, provided by the Central Statistical Office. On the basis of our comparisons, we argue that the growing prevalence of undeclared work has not resulted from unregistered activities of the unemployed. Therefore, we show that a significant part of informal activity occurs within registered entitles, what may provide an important lead in further studies on undeclared work in Poland.
Keywords: undeclared work; shadow economy; informal employment; grey economy